2004
DOI: 10.1108/13552540410526999
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking for comparative evaluation of RP systems and processes

Abstract: A geometric benchmark part is proposed, designed and fabricated for the performance evaluation of rapid prototyping machines/processes. The benchmark part incorporates key shapes and features of better-known benchmark parts. It also includes new geometric features, such as freeform surfaces, certain mechanical features and pass-fail features that are increasingly required or expected of RP processes/systems. The part is suitable for fabrication on a typical RP machines. In this paper, the application of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 12 publications
1
100
1
1
Order By: Relevance
“…46. AM benchmarks with design related features from [239] (top left), [196] (top right), [180] (bottom left), [63] (bottom center), and [363] (bottom right). Adapted from [239] and [363].…”
Section: Am Benchmarks For Materials and Machine Specific Consideratiomentioning
confidence: 99%
“…46. AM benchmarks with design related features from [239] (top left), [196] (top right), [180] (bottom left), [63] (bottom center), and [363] (bottom right). Adapted from [239] and [363].…”
Section: Am Benchmarks For Materials and Machine Specific Consideratiomentioning
confidence: 99%
“…Engine components, medical devices and manufacturing molds are some of the parts that can be manufactured through LOM. Previous work has demonstrated that LOM can successfully produce functional parts, for its dimensional accuracy, [8] and low surface average roughness in comparison with other AM techniques [9].…”
Section: Introductionmentioning
confidence: 99%
“…A secondary post-processing operation will be required to peel off the layered support material, so revealing the final part. This post-processing is usually cited as the main disadvantage of this technique [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many 3D printer experts and scholars 11,12,13,14,15 have studied and reported on strategies for selecting suitable 3D printers based on a given design. They have either limited their investigations to professional users or restricted their research to 3D printer parameters and part accuracies.…”
Section: Introductionmentioning
confidence: 99%